2018
DOI: 10.1186/s12910-018-0257-6
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia and assisted suicide for people with an intellectual disability and/or autism spectrum disorder: an examination of nine relevant euthanasia cases in the Netherlands (2012–2016)

Abstract: BackgroundEuthanasia and assisted suicide (EAS) have been legally possible in the Netherlands since 2001, provided that statutory due care criteria are met, including: (a) voluntary and well-considered request; (b) unbearable suffering without prospect of improvement; (c) informing the patient; (d) lack of a reasonable alternative; (e) independent second physician’s opinion. ‘Unbearable suffering’ must have a medical basis, either somatic or psychiatric, but there is no requirement of limited life expectancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 30 publications
0
61
0
6
Order By: Relevance
“…In two studies, people with ID were informed about their situation and their prospects (Van Thiel et al 1997;Tuffrey-Wijne et al 2018). In one study, this was done by 'sufficiently informing her at her own level' (Tuffrey-Wijne et al 2018). In another study, this process remained unclear (Van Thiel et al 1997).…”
Section: Goal Talk: Identify Discussion Partner and Identify Patient mentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies, people with ID were informed about their situation and their prospects (Van Thiel et al 1997;Tuffrey-Wijne et al 2018). In one study, this was done by 'sufficiently informing her at her own level' (Tuffrey-Wijne et al 2018). In another study, this process remained unclear (Van Thiel et al 1997).…”
Section: Goal Talk: Identify Discussion Partner and Identify Patient mentioning
confidence: 99%
“…Of the 10 included studies, eight were conducted in the Netherlands, one in Australia, and one in the United States. Six studies were (semi-structured) interview studies (Van Thiel et al 1997;Wagemans et al 2013a;Wagemans et al 2013b;Bekkema et al 2015;Zaal-Schuller et al 2016;Zaal-Schuller et al 2018), two included multiple case studies (Watson et al 2017;Tuffrey-Wijne et al 2018), one was a single case study (Lohiya et al 2003), and in one study, medical files were examined (Wagemans et al 2010). All studies had an observational design.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found six case reports of people with intellectual disability and three of people with autism spectrum disorder. We published our analysis of these reports last year (Tuffrey‐wijne, Curfs, Finlay, & Hollins, ); our study is briefly described in the longer version of the Eugenics position paper.…”
Section: Euthanasia In the Netherlandsmentioning
confidence: 99%
“…Accordingly, it became possible to consider the request of a person with IDD as valid in view of the established requirements. Thus a Dutch study reported nine cases involving seven persons with IDD in the period 2012–16 and found that a key problem was to determine in what sense and to what extent there was an explicit and repeated request that was actually understood as such by the person involved (Tuffrey‐Wijne, Curfs, Finlay, & Hollins, ).…”
Section: Legalized Euthanasia In the Netherlandsmentioning
confidence: 99%